Daniele Lorenzini, The Force of Truth. Critique, Genealogy, and Truth-Telling in Michel Foucault, The University of Chicago Press, Chicago and London 2023, pp. 198 - Mordacci, Roberto (Filosofia Morale/Moral Philosophy, 2024)